A Review on Thermophysical Properties for Heat Transfer Enhancement of Carbon‐Based Nanolubricant. Issue 10 (20th August 2021) - Saufi, Muhammad Aiman Bin; Mamat, Hussin Bin
Abstract : In previous years, nanolubricants have gained attention in terms of their use as heat transfer fluids in applications such as engine cooling and air conditioning. Carbon‐based nanolubricants have attracted great interest due to their superior heat transfer performance. To date, the stability of a carbon‐based nanolubricant is crucial if the enhanced properties are to be retained after the fabrication process. In this context, the current research aims to review the stability and thermophysical properties of carbon‐based nanolubricants. Recent works on these nanolubricants are summarized herein, including the method of preparation and improvements in their properties. The factors that affect the thermal conductivity and viscosity are also discussed, and finally, the applications of nanolubricants are described. The recent studies of nanolubricants are summarized and opportunities for further improvements in their efficiency are suggested. Abstract : A comprehensive analysis of the stability and thermophysical properties of carbon‐based nanolubricants is conducted herein. Recent works on nanolubricants are summarized, including the method of preparation and improvements in their properties. The factors that affect the thermal conductivity and viscosity are also discussed, and finally, the applications of nanolubricants are described.